2019
DOI: 10.3390/w11020366
|View full text |Cite
|
Sign up to set email alerts
|

Biological Diversity in Headwater Streams

Abstract: Headwaters, the sources of all stream networks, provide habitats that are unique from other freshwater environments and are used by a specialised subset of aquatic species. The features of headwaters that provide special habitats include predator-free or competitor-free spaces; specific resources (particularly detrital based); and moderate variations in flows, temperature and discharge. Headwaters provide key habitats for all or some life stages for a large number of species across just about all freshwater ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 106 publications
2
50
0
Order By: Relevance
“…The link between soils and streams in terms of microbial communities has been investigated in the past using sequencing techniques (Crump et al 2012;Ruiz-González et al 2015;Savio et al 2015). However, few studies have investigated the temporal dynamics of bacterial abundances in streams (Hullar et al 2006;Richardson 2019). Here we found that high flow conditions, as they are commonly present in our study streams during rainstorms or snowmelt, caused a general increase in bacterial abundances (Fig.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The link between soils and streams in terms of microbial communities has been investigated in the past using sequencing techniques (Crump et al 2012;Ruiz-González et al 2015;Savio et al 2015). However, few studies have investigated the temporal dynamics of bacterial abundances in streams (Hullar et al 2006;Richardson 2019). Here we found that high flow conditions, as they are commonly present in our study streams during rainstorms or snowmelt, caused a general increase in bacterial abundances (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…As an alternative explanation, enrichment of DOC along the flow length could also be generated by enhanced primary production that enhances DOC concentrations, especially during spring and summer low flow (Harjung et al 2019). However, many previous studies have shown that first order streams presented very low autochthonous primary production that accounted for less than 5% of the annual organic carbon inputs in these ecosystems (Fisher and Likens 1973;Mulholland 1997;Richardson 2019). In addition, the fact that the increase was independent of season, i.e., that it was also present during the fall and winter, makes this explanation less probable.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Running waters are all vulnerable to anthropogenic use and alteration. Exploitation and contamination of GW and its subsequent impacts on springs and headwaters have been addressed in other articles in this series (e.g., [42,46]). Many of the same threats affect streams across the size spectrum (see Conservation Issues under Section 3.3).…”
Section: Streams (Rhithral)mentioning
confidence: 99%
“…We also briefly explore what can be done to protect or restore these ecosystems. We thus aim at addressing the multiplicity of still and running freshwater environments, from headwaters down to large rivers and lakes (papers published in the VSI are cited in the following): groundwater and dependent ecosystems, springs and spring-fed streams [40][41][42][43][44][45], headwaters [46,47], glacial streams [48], streams, large rivers, ancient and large lakes, high-mountain lakes, oxbow lakes, reservoirs, urban freshwater habitats (fwh) [49], mires [50], small wetland ecosystems [51], Boreal and Arctic fwh, Antarctic fwh, Mediterranean fwh, tropical fwh [52], arid-climate fwh ( Table 1; the ecosystem types addressed and flagship organisms are illustrated in Figures 1 and 2).…”
Section: Introductionmentioning
confidence: 99%